Fisheries eco-biology of beel Koshba in Naogaon District (University Journal of Zoology, Rajshahi University, 2010)
The physical conditions of Beel Koshba consisting of water temperature(25.36±5.12°C/day), water depth (204.96±110.36cm/month) and water transparency (30.91±6.78cm/day) were recorded. The chemical parameters of total hardness, alkalinity, pH, DO, CO2 andammonia were 146.60±13.36 mg/l, 143.30±9.33 mg/l, 7.05±0.75, 6.03±1.08 mg/l, 8.64±0.88 mg/land 0.73±0.31 mg/l respectively. A total of 54 species of different vegetations 123 species ofphytoplankton and 73 species of zooplankton were recorded from the beel. A total of 104 speciesof fish and Annelids (8), arthropods (12), molluscs (15), amphibian (8), reptiles (21), avis (40) andmammals (12) were identified. Pesticidal toxic effluents contexts were also observed in the beelecosystem.Key words: Fisheries; Eco-Biology; Beel KoshbaDOI: 10.3329/ujzru.v28i0.5283Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 33-39